Objek Wisata Permandian Air Panas Kea-Kea Di Kabupaten Kolaka Dengan Penekanan Arsitektur EcoTech - Eka Sinta Pratiwi Kamase, Tiwi; Nahdatunnisa; Elvina Sari Taufiq (Fakultas Teknik, Universitas Muhammadiyah Kendari, 2025)
The Kea-Kea Hot Springs in Kolaka Regency have great potential as a uniquenatural tourist destination with economic and cultural value. The developmentof this area needs to be designed with a sustainable approach in order topreserve the environment and provide comfort for visitors. This study aims toformulate a concept for the development of hot spring tourism with an emphasison eco-tech architecture, which is a combination of environmentally friendlytechnology, ecological principles, and the use of local materials. The methodsused include site surveys, analysis of existing conditions, literature studies, and aparticipatory approach through the involvement of the surrounding community.The expected results are a master plan design for the tourist area that combinesrecreational facilities, renewable energy management, sustainable water andwaste treatment systems, and integration with the natural landscape. With theapplication of the eco-tech architectural concept, this area is expected tobecome an environmentally friendly tourist destination that supports natureconservation, empowers local communities, and increases the tourist appeal ofKolaka Regency.